A Comparison of Three Ion Sensing Circuits in a Homogeneous Charge Compression Ignition Engine. Issue 8 (3rd August 2017) - Phan, Tung M.; Mack, J. Hunter; Butt, Ryan H.; Dibble, Robert W.
ABSTRACT: The use of a spark plug ion sensor to detect combustion timing in a homogeneous charge compression ignition (HCCI) engine is a technique that could alleviate the need for pressure transducers, a more expensive alternative. One disadvantage of this approach is the difficulty in obtaining a strong signal at lower equivalence ratios. This article addresses and compares three ion sensing circuitries, namely a voltage follower, a notch filter circuit that removes the 60-Hz wall noise, and a notch filter whose output is coupled to a custom-built "integrator" circuit. The circuit optimizations are aimed at improving signal strength and reliability. The ion signal present in the combustion chamber is experimentally investigated in a 1.9-L Volkswagen engine, modified for HCCI operation and fueled with gasoline. Experiments are conducted across different intake temperatures, pressures, and equivalence ratios. It was found that the custom-built circuit provided the best ion signal strength and reliability.